Kinetics of electron cooling in metal films at low temperatures and revision of the two-temperature model. (28th June 2018) - Bezuglyj, A I; Shklovskij, V A
Abstract: The two-temperature model (2TM) introduced by Kaganov, Lifshitz, and Tanatarov is widely used to describe the energy relaxation in the electron–phonon system of a metallic film. At the same time, the accuracy of the description of the electron–phonon system in terms of the 2TM, i.e. on the basis of the electron and phonon temperatures, has not been considered in detail until now. In this paper we present a microscopic theory of cooling of instantly heated electrons in metallic films. In framework of this theory the main features of electron cooling in thick and thin films were found, and an analysis of the accuracy of the 2TM in the low-temperature region was carried out. We consider a more accurate three-temperature model, which (in contrast to the 2TM) explicitly takes into account phonons with angles of incidence exceeding the angle of total internal reflection. The contribution of these phonons to the kinetics of electron relaxation can be significant if the sound velocities in the film and the substrate are quite different.